Broadcast Spectrum Fees Administration and Congressional Proposals and Pro-Con Discussion. - Library of Congress. Congressional Research Service ([S.l] : [s.n.], 1992)
Reviews the debate over whether fees should be collected from broadcasters and other users of the electromagnetic spectrum. Discusses pros and cons of recent proposals by the administration and Congress to implement a schedule of flat fees for selected electromagnetic spectrum users.
Record is based on bibliographic data in ProQuest U.S. Congressional Research Digital Collection (last viewed July 2010). Reuse except for individual research requires license from ProQuest, LLC.
CRS Report.
Keywords: Telecommunication; User charges